Oxidised plant sterols as well as oxycholesterol increase the proportion of severe atherosclerotic lesions in female LDL receptor+/ − mice. Issue 1 (18th June 2013) - Plat, Jogchum; Theuwissen, Elke; Husche, Constanze; Lütjohann, Dieter; Gijbels, Marion J. J.; Jeurissen, Mike; Shiri-Sverdlov, Ronit; van der Made, Ingeborg; Mensink, Ronald P.
Abstract : Oxysterols (oxidised cholesterol) may play a role in the pathogenesis of CVD. Similar to cholesterol, plant sterols are susceptible to oxidation. However, less is known about the potential atherogenicity of oxidised plant sterols (oxyphytosterols). In the present study, the atherogenicity of a mixture of oxyphytosterols was examined by feeding female LDL receptor-deficient (LDLR +/ − ) mice for 35 weeks a control diet (atherogenic high-fat diet; n 9), an oxysterol diet (control diet+0·025 % (w/w) oxysterols; n 12) or an oxyphytosterol diet (control diet+0·025 % (w/w) oxyphytosterols; n 12). In the LDLR +/ − mice, serum levels of cholesterol, lipoprotein profiles, cholesterol exposure and inflammatory markers at the end of the experiment were comparable between the three diet groups. Nevertheless, the proportion of severe atherosclerotic lesions was significantly higher after oxysterol (41 %; P = 0·004) and oxyphytosterol (34 %; P = 0·011) diet consumption than after control diet consumption (26 %). Oxyphytosterol levels in the lesions were the highest in the oxyphytosterol group. Here, we show that not only dietary oxysterols but also dietary oxyphytosterols increase the proportion of severe atherosclerotic lesions. This suggests that plant sterols when oxidised may increase atherosclerotic lesion severity instead of lowering the size and severity of lesions when fed in their non-oxidised form. Therefore, this finding might give an indication as to where to find the answer in the current hot debate about the potential atherogenicity of plant sterols. However, to what extent these results can be extrapolated to the human situation warrants further investigation.